Hedgehogs and other insectivores : [book author, Steven Otfinoski]. - Otfinoski, Steven; World Book, Inc. (Chicago : World Book, 2000)
Questions and answers explore the world of insectivores, with an emphasis on hedgehogs.
Includes index.
Keywords: Hedgehogs -- Juvenile literature; Insectivores (Mammals) -- Juvenile literature; Hedgehogs -- Miscellanea; Insectivores -- Miscellanea; Questions and answers